Diagnóstico comunitario de salud del Barrio Labanda sector alto VII, septiembre-diciembre de 2013 - Chamba Cajamarca, Hilda Noemí (2013)
The study was of descriptive type, he/she makes emphasis in the analysis and interpretation of the facts; the methodology relied on strategies settled down in the Pattern of Integral Attention of Health, such as: it visits domiciliary to apply the family record, and it guides of interview that it allowed to complete the information for the base line, where high-priority problems were identified to take technical decisions and appropriate politicians to the local reality looking for to optimize the institutional answers and to propitiate the community participation in the improvement of the conditions of health. (Guerrero and Slimming 2009:4). The universe was constituted by 59 families and 258 inhabitants, among the most outstanding data indicators stand out as prevalencia of masculine sex 54,26%, basic education level 42,25%, school and adolescents with nutritional good state 97,78%, immunizations in smaller than 5 years 93,55%, family planning the method of the rhythm is the more used with 52,94%, he/she was also 3 illiterates, as for the epidemic profile of the chronic illnesses HTA stands out with 4,65% and the intellectual discapacidad with 0,78%. Key Words: Community diagnosis of health, Epidemic Profile